2022
DOI: 10.1037/edu0000755
|View full text |Cite
|
Sign up to set email alerts
|

How students perform synthesis tasks: An empirical study into dynamic process configurations.

Abstract: In this study we examine process configurations in synthesis tasks. We study whether these configurations are students traits or vary within students per task. In a national survey with a representative sample of 658 Dutch upper-secondary school students, we collected writing tasks, registered students’ writing behaviors (via keylogging) and their task perceptions and assessed the quality of their texts. Each participant completed two informative and two argumentative synthesis tasks. Writing process configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…The rationale is the following: when giving feedback on specific writing process variables, we may expect to find an effect of the feedback on these writing process variables. Secondly, from previous research we know that these process variables are correlated with text quality (see, e.g., Vandermeulen, van den Broek, et al (2020) for source-related variables and Van Steendam et al (2022) and Van Waes & Leijten (2015) for fluency-, pausing-, and revision-related variables). For this reason, these variables were also incorporated into the Inputlog writing process report.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale is the following: when giving feedback on specific writing process variables, we may expect to find an effect of the feedback on these writing process variables. Secondly, from previous research we know that these process variables are correlated with text quality (see, e.g., Vandermeulen, van den Broek, et al (2020) for source-related variables and Van Steendam et al (2022) and Van Waes & Leijten (2015) for fluency-, pausing-, and revision-related variables). For this reason, these variables were also incorporated into the Inputlog writing process report.…”
Section: Methodsmentioning
confidence: 99%
“…Du and List (2020) also found that American undergraduate students were not able to effectively connect various information between notes taken and writing episodes made during a read-to-write task. Recently, Van Steendam et al (2022) explored a large sample of 658 Dutch upper secondary students' synthesis writing process and found that higher-level writers tended to rely on fewer integration activities (e.g., less time in reading sources or switches between written products and sources).…”
Section: The Integration Process Of Iwmentioning
confidence: 99%
“…Extant studies have argued that the capacity to write from sources goes far beyond the combination of independent literacy skills such as listening, reading, and writing (Chan, 2017; Liao et al, 2021; Zhu et al, 2016). When tackling this task, students are typically required to utilize integration skills to incorporate various pieces of information from multiple source materials into a new text (Cumming et al, 2016; Plakans & Gebril, 2013; Van Steendam et al, 2022). The process of integrating information indeed characterizes the IW task as a complicated literacy activity, involving selecting (distilling key ideas from less important details), organizing (making meaning of texts and reconstructing the meaning), and connecting (linking information from various sources (Nelson & King, 2022; Spivey, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations